If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + (b + 1) + (c + 2) = 222 Reorder the terms: a + (1 + b) + (c + 2) = 222 Remove parenthesis around (1 + b) a + 1 + b + (c + 2) = 222 Reorder the terms: a + 1 + b + (2 + c) = 222 Remove parenthesis around (2 + c) a + 1 + b + 2 + c = 222 Reorder the terms: 1 + 2 + a + b + c = 222 Combine like terms: 1 + 2 = 3 3 + a + b + c = 222 Solving 3 + a + b + c = 222 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + a + b + -3 + c = 222 + -3 Reorder the terms: 3 + -3 + a + b + c = 222 + -3 Combine like terms: 3 + -3 = 0 0 + a + b + c = 222 + -3 a + b + c = 222 + -3 Combine like terms: 222 + -3 = 219 a + b + c = 219 Add '-1b' to each side of the equation. a + b + -1b + c = 219 + -1b Combine like terms: b + -1b = 0 a + 0 + c = 219 + -1b a + c = 219 + -1b Add '-1c' to each side of the equation. a + c + -1c = 219 + -1b + -1c Combine like terms: c + -1c = 0 a + 0 = 219 + -1b + -1c a = 219 + -1b + -1c Simplifying a = 219 + -1b + -1c
| 1/2(70)+10=-25 | | 17+12x-4=19x+25-13x | | (3x-2y)= | | 2x=7y+4 | | 6x-28=28+4x | | y=5+6.25 | | 101+3y=1-17y | | p/7=5.4 | | 3c+2b=75.44 | | H(4)=0 | | 3a-9=5a-8 | | n-4.1=-9.6 | | 2b-6-5b-3= | | 6y-3(x-2y)= | | 7=1/2m+9. | | 9+2x=45 | | 2x+7=84 | | 315=6x^2+3x | | -3(2w-4)+6w=6+2(3w-2) | | -10x+2y=-30 | | y=0+6.25 | | A+16=74 | | 3x+2y=-43 | | 5y+3=7y-4 | | -5/6w=-3/5. | | m-13.5=-16.5. | | 0=0.50x+6.25 | | 7(w-1)=8w+6-5(-3w-1) | | x^2+36=169 | | 34-29=7 | | x^2+81=169 | | (5a+7)(a+5)=32 |